Relationship between Physical Workload and Thermal Work Environment with Dehydration in Laundry Operators - Reyna Sandrawati Cintya Dewi; Corie Indria Prasasti (Pancasakti Journal Of Public Health Science And Research, 2025)
The production process at PT. K, a garment company in Malang, relies on manual equipment and human labor, exposing workers to physical strain and heat. Prolonged exposure to high temperatures can impair performance, accelerate fatigue, and increase the risk of dehydration. However, research on hydration status among laundry workers in the garment industry remains limited. This study aimed to examine the relationship between physical workload and the thermal work environment with hydration status among laundry workers at PT. K. This analytical cross-sectional study applied a total sampling method with 31 respondents. Data were analyzed using Spearman’s rank correlation test. Results showed no significant correlation between physical workload and hydration status (r = 0.302, p = 0.099), while a significant positive correlation was found between the thermal work environment and hydration status (r = 0.562, p = 0.001). In conclusion, thermal conditions were strongly associated with dehydration, whereas physical workload showed no significant relationship.